Analisis Biaya Manfaat dan Strategi Pengendalian Penyakit Antraks di Pulau Sumbawa Provinsi Nusa Tenggara Barat (COST BENEFIT ANALYSIS AND STRATEGY OF ANTHRAX CONTROLLING AT SUMBAWA ISLAND, PROVINCE OF WEST NUSA TENGGARA) - Kusbianto, Erwin; Pribadi, Eko Sugeng; Siregar, Abdulgani Amri (Jurnal Veteriner, 2013)
Sumbawa Island is an anthrax endemic area. One of the efforts for anthrax control is byvaccination, particularly in cattle and buffalo. The purpose of this research was to conduct costbenefitanalysis of the two scenarios of anthrax control in Sumbawa Island, namely Program A,anthrax control program has been conducted at this time on Sumbawa Island with vaccinationcoverage < 50% compared with Program B, anthrax control that are intended to reduce the prevalenceby vaccination coverage > 80%, and to analyze the anthrax control strategies in Sumbawa Island.The results of cost-benefit analysis of anthrax control in cattle and buffalo were : both programsprovided positive net present value (NPV) and internal rate of return (IRR) which were greaterthan the discount rate, but the criteria for B/C ratio of program A was > 1 on the discount rate of15% and 20%, while the B/C ratio > 1 of program B was only obtained in buffaloes with a discountrate of 15%. By considering the three criterias of cost-benefit analysis, it can be stated that theanthrax control in Sumbawa Island with vaccination coverage < 50% is a proper and more efficientcontrol compared to anthrax control with coverage > 80% or without control.
Keywords: Anthrax, Cost Benefit Analysis, Sumbawa Island